Hierarchical structuring of knowledge in basketball game - Trninic, S.; Trninic, M.; Jelaska, I. (Acta Kinesiologica, 2010)
The purpose of this study is to identify and explain hierarchical structure of knowledge in basketball game that can be applied to the entire formal tree model in sport games with the ball. Structural approach was used in the analysis of knowledge in basketball game. Here knowledge is shown as a hierarchical structured binary tree. The basic categories of the tree in this hypothetical model from the hierarchical viewpoint are: strategy, tactics, state of the game, jobs in the game, basic elements and techniques of the game and individual tactics. Furthermore, it is important to emphasize that the central point in this study belongs to jobs in the game, which are defined as an ordered series of game's basics. In top sports, it is necessary to apply the methodology for assessing the knowledge and skills based on theory of time series. On the other hand, basketball as a complex sporting activity was treated as an ordered series of tasks in the game. Here expert coaches should concentrate on evaluation of each type of player compared to the success of doing business in the game. It is believed that hierarchical structure of knowledge in basketball game forms the basis for implementation of research knowledge of structural analysis in other sports games with the ball.